Answer:
![x=(3)/(5)](https://img.qammunity.org/2022/formulas/mathematics/high-school/xok35fy6yqfar407vjuj9vnoxym1i8try8.png)
x = - 1
Explanation:
5x² + 2x - 3 = 0
5x² + 2x - 3x = 0
(5x² + 5x) + (- 3x - 3) = 0
5x(x + 1) - 3(x + 1) = 0
(5x - 3)(x + 1) = 0
Create separate equations.
5x - 3 = 0
x + 1 = 0
5x - 3 = 0
5x - 3 + 3 = 0 + 3
5x = 3
5x ÷ 5 = 3 ÷ 5
![x=(3)/(5)](https://img.qammunity.org/2022/formulas/mathematics/high-school/xok35fy6yqfar407vjuj9vnoxym1i8try8.png)
x + 1 = 0
x + 1 - 1 = 0 - 1
x = - 1